Pengaruh Pendidikan Breastfeeding Father terhadap Dukungan Ayah dalam Pemberian ASI pada Ibu Postpartum di RSU Muslimat Ponorogo - Kun Marátin Sholikhah; Tut Rayani Aksohini Wijayanti (Journal of Innovative and Creativity, 2025)
Exclusive breastfeeding during the first six months of life is crucial for ensuring optimal infant growth and preventing various diseases. The success of breastfeeding is not determined solely by the mother, but is also influenced by the husband’s involvement as a Breastfeeding Father. This study aims to examine the effect of Breastfeeding Father education on fathers’ support in exclusive breastfeeding. The research employed a quasi-experimental approach using a one-group pretest–posttest design. A total of 49 respondents were selected through purposive sampling. Data were collected using a questionnaire assessing fathers’ knowledge and support related to breastfeeding, and were analyzed using the Wilcoxon test. The findings demonstrated a significant effect of Breastfeeding Father education on increasing paternal support in exclusive breastfeeding (Z = –4.094; p < 0.001). Fathers’ support improved markedly after the educational intervention. Further analysis indicated that enhanced paternal knowledge directly contributed to stronger emotional and practical support for mothers. This study concludes that the husband’s involvement plays a vital role in the success of exclusive breastfeeding, and the results highlight the importance of implementing structured educational programs for fathers to strengthen exclusive breastfeeding outcomes.